Performance of additional colonoscopies and yield of neoplasms within 3 years after screening colonoscopy: a historical cohort study - Stock, C.; Hoffmeister, M.; Birkner, B.; Brenner, H. (Endoscopy, 2013)
Background and study aims: After screening colonoscopy, additional colonoscopies may be required for adenoma surveillance or diagnostic reasons. The aim of the present study was to explore their utilization and findings in routine practice.Patients and methods: The study comprised an historical cohort of individuals participating in colonoscopy screening in 2006. Utilization and yield of neoplasms of additional colonoscopies performed in these individuals by the same physician ( < 6 months and 6 – 36 months after screening) between 2006 and 2009 were assessed using data of a colonoscopy quality assurance program in Bavaria, Germany. Screening including polypectomy, and short-term follow-up colonoscopy was assumed to have been completed within ≤ 6 months. Multivariate logistic regression was used to identify predictors of additional colonoscopy and advanced neoplasms (high risk adenoma or colorectal cancer [CRC]) among those with additional colonoscopy during the period of 6 – 36 months after screening. Results: A total of 51 301 individuals undergoing screening colonoscopy were included. Of these, 10.1 % (95 % confidence interval [CI] 9.8 % – 10.3 %) had an additional colonoscopy performed by the same physician between 6 and 36 months after screening. The percentages of those with additional colonoscopy were 5.7 % (95 %CI 5.5 % – 5.9 %), 18.6 % (95 %CI 17.8 % – 19.4 %), and 33.7 % (95 %CI 32.2 % – 35.2 %) after negative screening, low risk adenoma at screening, and high risk adenoma at screening, respectively. The overall findings were negative colonoscopy, low risk adenoma, high risk adenoma, and CRC in 68.6 % (95 %CI 67.3 % – 69.8 %), 24.1 % (95 %CI 23.0 % – 25.3 %), 6.7 % (95 %CI 6.0 % – 7.4 %), and 0.6 % (95 %CI 0.4 % – 0.8 %), respectively. Younger age, male sex, screen-detected adenomas, inflammatory bowel disease, and early repeat colonoscopy within 6 months were predictors of additional colonoscopy. Older age, male sex, screen-detected adenomas, and surveillance indications were associated with increased risk of advanced neoplasms at post-screening colonoscopy.Conclusion: The results indicate frequent utilization of additional colonoscopies along with substantial adenoma yield in the first 3 years after screening colonoscopy.